The interdisciplinary horizon, a dissident bet: The interdisciplinary horizon, a dissident bet - GARCÍA BRAVO, María Haydeé (Utopía y Praxis Latinoamericana, 2021)
In this text I expose the experience of the Diplomado in Professional Updating in Interdisciplinary Research at the Center for Interdisciplinary Research in Sciences and Humanities at UNAM, which was a training and updating program in interdisciplinary. I discuss some conceptions about interdiscipline to outline this proposal as a dissident. Understanding interdisciplinary work as the formation of working teams in order to address problems conceptualized as complex sistems and by acquiring skills for the collaborative teamwork.I highlight the importance of the collective construction of common-epistemic framework, that is, the explicitness of the values and ontological commitments that guide the research.